Analysis of Leakage Loss in Silicon Photonics with Finite Gain Compensation - Po-Jui Chiang; Tien-Tsorng Shih (IEEE Photonics Journal)
Silicon waveguides fabricated on silicon-on-insulator wafers are leaky in nature. This fact puts a lower bound on the insulator thickness in silicon photonic structures as integrated with compact electronic devices. We examine this constraint from the angle of finite gain compensation for leakage loss using III-V semiconductor gain media bonded to passive silicon waveguides. With a reasonable magnitude of available gain, we find that an insulator layer thinner than 320 nm could support the fundamental quasi-transverse-electric mode of silicon waveguides with a core thickness around 170 nm. This may enable the integration of photonic devices with compact electronic counterparts for radio-frequency and analog applications. Furthermore. size reductions to the level of partially depleted electronic devices might be possible if the leakage loss need not be fully compensated, or the gain limit could be raised